2017
DOI: 10.1007/s00134-017-4880-3
|View full text |Cite
|
Sign up to set email alerts
|

Early goal-directed nutrition versus standard of care in adult intensive care patients: the single-centre, randomised, outcome assessor-blinded EAT-ICU trial

Abstract: EGDN did not appear to affect physical quality of life at 6 months or other important outcomes as compared to standard nutrition care in acutely admitted, mechanically ventilated, adult ICU patients. Clinicaltrials.gov identifier no. NCT01372176.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
256
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(293 citation statements)
references
References 40 publications
4
256
0
20
Order By: Relevance
“…As reported in multiple studies, we also found energy overfeeding to be associated with higher mortality in non‐sepsis patients . Furthermore, we did not find a survival benefit for early medium (80%–110%) energy intake compared with early low energy intake, in line with recent RCTs …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As reported in multiple studies, we also found energy overfeeding to be associated with higher mortality in non‐sepsis patients . Furthermore, we did not find a survival benefit for early medium (80%–110%) energy intake compared with early low energy intake, in line with recent RCTs …”
Section: Discussionsupporting
confidence: 90%
“…For energy intake, recent RCTs do not report survival benefit of early provision of approximately 100% of energy expenditure compared with lower energy intakes . Furthermore, overfeeding (>110%) has been associated with increased morbidity and mortality .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several experts have suggested that the feeding target should be determined by indirect calorimetry rather than by a formula . Nevertheless, 3 recent RCTs that used indirect calorimetry in the intervention group did not find any benefit of such strategy . Moreover, aggregating the results of these trials suggested that individualized nutrition, which led to an increased feeding dose, was ineffective …”
Section: Results From Recent Feeding Rctsmentioning
confidence: 99%
“…Similarly, in the PEPaNIC study, urea levels significantly increased by administering early PN, with an increased need for renal replacement therapy . Likewise, the Intravenous Amino Acid Therapy for Kidney Function in Critically Ill and (Nephro‐Protective) the Early Goal‐Directed Nutrition Versus Standard of Care in Adult Intensive Care Patients (EAT‐ICU) trials revealed increased ureagenesis by giving more amino acids …”
Section: Mechanisms Explaining Why Early Feeding Has Failed To Benefimentioning
confidence: 95%
“…This conclusion applies to the design and interpretation of prospective clinical trials. Two recent clinical outcome RCTs compared moderate protein and full calorie provision with permissive underfeeding; the results were disappointing . When clinical trial designs like these are used, the harmful effects of full energy provision (and its associated large fluid volumes) could well negate the benefits of more generous protein provision.…”
Section: Permissive Underfeeding and Clinical Outcomesmentioning
confidence: 99%